PENGARUH KOMISARIS INDEPENDEN DAN LAINNYA TERHADAP NILAI PERUSAHAAN - Kurniawan, William Angelo; Zubaidi, Umar Issa (E-Jurnal Akuntansi TSM, 2025)
This study aims to examine the effect of independent commissioners, institutional ownership, audit committees, managerial ownership, the presence of female board members, and capital structure on firm value in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period. The research employed a quantitative approach with a causal design. The sample was selected using purposive sampling, resulting in 61 companies with 183 data observations. Data were analyzed using multiple linear regression with Robust Standard Errors (RSSE) due to the presence of heteroskedasticity. The findings indicate that, simultaneously, the model is not significant. Partially, only the capital structure is found to have a positive and significant impact on firm value, while the other five good corporate governance variables (independent commissioners, institutional ownership, audit committees, managerial ownership, female board members) show no significant effect. These results suggest that in the context of corrected heteroskedasticity, investors tend to prioritize financial structure considerations over GCG mechanisms when assessing a company’s prospects.